George Fielding Eliot papers - Eliot, George Fielding, 1894-1971.
Correspondence, diary, speeches, drafts of radio broadcasts, writings, articles, notes, newspaper clippings, and printed matter relating primarily to Eliot's career as a newspaper columnist, contributor to periodicals, and military editor of Collier's Encyclopedia. Pertains to his syndicated newspaper column, The Military Scene, and his contributions to periodicals including The American Legion Magazine, Family Weekly, The National Guardsman, National Review, and Suburbia Today. Subjects include the military and naval history of the American Revolution, Civil War, and World War II; the Vietnam War; prisoners of war in Vietnam; nuclear weapons; arms development in the Soviet Union, China, and the United States; arms limitation; national defense in the Cold War; military intelligence; the National Guard; and American suburban life. Correspondents include Arleigh A. Burke, Wallace Martin Greene, W. Barton Leach, Sir John Cotesworth Slessor, and Charles A. Weil.
Library of Congress Motion Picture, Broadcasting and Recorded Sound Division.
Library of Congress Prints and Photographs Division.
Author, journalist, and military analyst.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Burke, Arleigh A., -- 1901- -- Correspondence; Greene, Wallace Martin, -- 1907- -- Correspondence; Leach, W. Barton -- 1900- -- Correspondence; Slessor, John Cotesworth, -- Sir, -- 1897- -- Correspondence; Weil, Charles A. -- Correspondence; American Legion magazine; Collier's encyclopedia; Family weekly; National guardsman; National review; Suburbia today; American newspapers -- Sections, columns, etc; American periodicals; Arms race -- China; Arms race -- Soviet Union; Arms race -- United States; Cold War; Disarmament; Encyclopedias and dictionaries; Journalism, Military -- United States; Military intelligence; Nuclear weapons; Radio scripts; Suburban life -- United States; Suburbs -- United States; Vietnam War, 1961-1975.; Vietnam War, 1961-1975 -- Prisoners and prisons; World War, 1939-1945.; United States -- Defenses; United States -- History -- Revolution, 1775-1783.; United States -- History -- Civil War, 1861-1865.; United States -- History, Military; United States -- History, Naval; United States -- Militia -- Periodicals; United States -- National Guard; Authors; Journalists; Military analysts